Fenologia y desarrollo de las agallas de las ramas del guisaro (Psidium guineense Swartz) (Myrtaceae) y su relación con varias especies de Microhimenopteros en Heredia, Costa Rica. - Suárez, Edgar; Esquivel, Carlos (Uniciencia, 1991)
Development of the stem galls of Psidium guineense and phenology of four species of micro hymenopteran wasps that inhabited the galls were studied during 17 months (April 1985 to August 1986) in a natural population of Psidium in Barva, Heredia Province, Costa Rica.Gall formation started in July, their number progressively increasing until December of the same year. A new period of gall formation started in July of the following year. The variations in size and external appearance of the galls, as well as the pattern of wasp emergence, suggest that the galls pass through three stages during their development which are described in detail. The wasps emerged from the galls between October and July of the following year. Four species of micro hymenopterans emerged (in order of Abundance): Chrysonotomya sp. (Eulophidae), Sycophila (= Eudecatoma) sp. (Eurytomidae), Torymoides (= Dimeromicrus) sp. And Torymus sp. (Torymidae). Chrysonotomya sp had a peak of emergence in May and probably is the gall maker. The other species had their peaks of emergence in April and are probably parasitoids on Chrysonotomya sp.